Underwater Bending Actuator Based on Integrated Anisotropic Textile Materials and a Conductive Hydrogel Electrode - Sascha Pfeil; Alice Mieting; Rebecca Grün; Konrad Katzer; Johannes Mersch; Cornelia Breitkopf; Martina Zimmermann; Gerald Gerlach (Actuators, 2021)
Electroactive polymers (EAPs), especially dielectric elastomer actuators (DEAs), belong to a very promising and emerging class of functional materials. While DEAs are mostly utilized to rely on carbon-based electrodes, there are certain shortcomings of the use of carbon electrodes in the field of soft robotics. In this work we present a fish-like bending structure to serve as possible propulsion element, completely avoiding carbon-based electrodes. The presented robot is moving under water, using a particularly tailored conductive hydrogel as inner electrode and a highly anisotropic textile material to manipulate the bending behavior of the robot. The charge separation to drive two DEAs on the outsides of the robot is provided by the conductive hydrogel while the surrounding water serves as counter electrode. To characterize the hydrogel, tensile tests and impedance spectroscopy are used as measurement methods of choice. The performance of the robot was evaluated using a digital image correlation (DIC) measurement for its bending deflections under water. The developed fish-like robot was able to perform a dynamic bending movement, based on a tri-stable actuator setup. The performed measurements underpin the sufficient characteristics for an underwater application of conductive hydrogel electrodes as well as the applicability of the robotic concept for under water actuations.